Being and becoming third-space professionals: a case study from low-and-middle income countries - Azra Naseem; Jannat Karim Khan; Tashmin Khamis; Jane Rarieya (Journal of Learning Development in Higher Education)
This case study explores the authors’ experiences of establishing the identity of third-space professionals at a multi-country university with campuses on three continents. In particular, it draws on their identities and experiences as female leaders in educational development. Using autoethnography, the authors reflect on their experiences to identify issues, strategies, and areas for further development regarding third-space professionals’ identities, particularly with regard to women. As the concept of third-space professionals is relatively new in Low- and Middle-Income Countries (LMICs) where the university is located, this journey of becoming and being third-space professionals was fraught with challenges that question traditional norms within academia and their culture, requiring innovative problem-solving, continuous learning and accountability. Establishing this new identity involved extensive negotiations to create a new professional stream, gaining recognition from university leaders, and advocating for career pathways. Recognising the demands on third-space women leaders in our contexts, the case study also underscores the importance of workplace structures that support those who work in this critical area. The insights gained may be helpful to others seeking to establish third-space professionals in their professional contexts.